Is Online Learning Effective Implemented in the Outbreak of Covid-19? (An Evaluation Approach in the Vocational High Schools) - Dwi Novita Sari; Syukrul Hamdi (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
The online learning policy has been implemented in Indonesia at all levels of education since March 2020 to prevent the COVID-19 pandemic from spreading. This study aims to evaluate the implementation of accounting learning with an online system using the CIPP (Context, Input, Process, Product) evaluation model. The research subjects consisted of 14 teachers and 256 Vocational High School (VHS) students majoring in Accounting and Finance in Purworejo Regency. The analysis technique used questionnaires and documentation. The results showed that: (1) the success rate of the online accounting learning system in the context aspect obtained a mean score of 3.07 (76%) with a good category; (2) the success rate of online accounting learning system on the input aspect obtained a mean score of 2.81 (72)% in a good category; (3) the success rate of online system accounting learning in the process aspect obtained a mean score of 2.76 (67%) with a good category; (4) the success rate of the online accounting learning system in the product aspect obtains a mean score of 2.98 (75%) with a good category. Based on the results of the study, it can be concluded that the implementation of online system accounting learning during the COVID-19 pandemic is in a good category.